The Actualization of Islamic Communication in Muslim Families: Perspectives from Exemplary Households and the Practice of Polygamy - Ade Rachmat Yudiyanto; Abdullah (Faculty of Law, Universitas Pekalongan, 2025)
Communication within the family constitutes a fundamental pillar in fostering domestic harmony, particularly within Muslim households that are grounded in Islamic values. This article aims to analyze how the principles of Islamic communication are actualized in family life, focusing on two central themes: the ideal model of a family and the practice of polygamy. Employing a qualitative-descriptive approach based on Islamic literature and family sociology, this study explores key principles of Islamic communication, such as qawlan sadīdan (truthful speech), qawlan ma‘rūfan (kind speech), and qawlan layyinan (gentle speech), within the relational dynamics of spouses and family members. In examining the case of polygamy, the article addresses the tension between normative religious teachings and practical realities, highlighting the communicative challenges that often arise in such familial contexts. The findings suggest that the effective actualization of Islamic communication is significantly influenced by the level of religious understanding, local cultural norms, and gender sensitivity. In conclusion, Islamic communication within the family is not merely rhetorical; it is an ethical praxis capable of shaping the family into a harmonious, just, and spiritually enriched social institution.